2013
DOI: 10.1080/03323315.2013.823273
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education level and type on moral reasoning

Abstract: The importance of education in developing morally sensitive individuals who use principled moral reasoning when facing dilemmas has been widely acknowledged. In the context of the criticism levelled at the Irish higher education system for failing to fulfil the role of intellectual leader and moral critic within the public domain, this paper examines the impact of education level (both undergraduate and post-graduate) and type (arts or technical/profession-based) on moral reasoning using 311 Irish participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…The teacher prepares various reasons that can be chosen by students by considering the characteristics of elementary school students who are still at a concrete operational stage [29]. Each answer that the students choose is a picture of moral judgment that has been developed by James Rest [21].…”
Section: Discussionmentioning
confidence: 99%
“…The teacher prepares various reasons that can be chosen by students by considering the characteristics of elementary school students who are still at a concrete operational stage [29]. Each answer that the students choose is a picture of moral judgment that has been developed by James Rest [21].…”
Section: Discussionmentioning
confidence: 99%
“…5 Menyadari pentingnya kesadaran moral bagi profesi tidak hanya dalam relasi dokterpasien, tetapi juga sebagai salah satu penentu performa klinis, penurunan kesadaran moral seiring dengan bertambahnya masa kuliah kedokteran adalah sebuah keprihatinan yang perlu ditemukan penyebabnya. 6 Karena belum banyak penelitian tentang kesadaran moral pada mahasiswa kedokteran di Indonesia, masih sulit disimpulkan apakah meningkat atau menurun seiring bertambahnya masa kuliah. DAFTAR PUSTAKA…”
Section: Pendahuluanunclassified
“…They actually reported that youngsters are more familiar in this respect. An explanation of these may be based on the findings of Doyle & O'Flaherty [36], who supported that higher level of education does not add to lower education level student achievements in terms of computer usage due to the nature of contents of curriculum at these levels.…”
Section: Computer Usage and Securitymentioning
confidence: 99%
“…Another plausible explanation for our finding may be based on Siponen [47] that public may consider awareness in different depths depending on the level of education because web security falls outside the scope of the traditional computer issues. On the other hand, Doyle & O'Flaherty [36] pointed out that education level impacts moral reasoning. Accordingly, the findings in our study possibly illustrate the due effects of the improved reasoning and interpretation skills with the education level.…”
Section: Web Usage and Securitymentioning
confidence: 99%
See 1 more Smart Citation